Group Counseling on Increasing the Learning Motivation of Broken Home Students - Lestari , Mardi; Hasan, Hasan; Silalahi, Micha Felayati; Thalib, Muh Mansyur; Ampulembang, Jessy Angel Casey; Kushendar, Kushendar (Grief and Trauma, 2023)
The problem in this research is that students' learning motivation after attending group counseling services is higher when compared to before attending group counseling services. The main objective of this research is to increase the learning motivation of broken-home students. Subjects in this study were 6 students. The main instrument used in this research is the learning motivation questionnaire. Research data were analyzed with descriptive analysis and inferential analysis using the Wilcoxon sign rank test formula. The results of the descriptive analysis showed that before attending group counseling services, 3 students had low learning motivation, and 3 students who had very low learning motivation. After participating in group counseling services, there was an increase in student learning motivation, namely, 1 student had very strong learning motivation, 2 students had strong learning motivation, 3 students had low learning motivation. The results of the inferential analysis show that the classification of students' learning motivation at SMK Negeri 1 Tana Toraja after attending group counseling services is higher than before attending group counseling services.